2010
DOI: 10.1111/j.1365-2621.2010.02354.x
|View full text |Cite
|
Sign up to set email alerts
|

Production of soya milk containing low flatulence‐causing oligosaccharides in a packed bed reactor using immobilised α‐galactosidase

Abstract: Peanut a-galactosidase was immobilised in calcium alginate beads and used to hydrolyse the flatulencecausing oligosaccharides, raffinose and stachyose, in soya milk in batch and in packed bed reactor with recycle. The immobilised enzyme exhibited a slightly lower activity than the free enzyme. The activity yield of immobilised a-galactosidase was 75.1% and the immobilisation yield was 82.6%. Batch hydrolysis using immobilised enzyme at 55°C resulted in 96% reduction in the oligosaccharides after 12 h. For the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Moreover, in this study, the immobilized α‐galactosidases were found to exhibit better hydrolysis of RFOs in soy milk in shorter period as compared to several earlier reported studies. The immobilized α‐galactosidase from peanut was shown to hydrolyze 96% oligosaccharides after 12 hr while cicer α‐galactosidase was able to degrade 70% RFOs in soy milk after 8 hr (Rajan & Nair, ; Singh & Kayastha, ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in this study, the immobilized α‐galactosidases were found to exhibit better hydrolysis of RFOs in soy milk in shorter period as compared to several earlier reported studies. The immobilized α‐galactosidase from peanut was shown to hydrolyze 96% oligosaccharides after 12 hr while cicer α‐galactosidase was able to degrade 70% RFOs in soy milk after 8 hr (Rajan & Nair, ; Singh & Kayastha, ).…”
Section: Resultsmentioning
confidence: 99%
“…A high temperature will speed up the conversion of substrate to product. However, too high of a temperature can induce the irreversible denaturation of an enzyme . The effects of temperature on the activity of free and HHDH@ES‐103B were researched at various temperatures (35–80°C) and the results are presented in Figure a.…”
Section: Resultsmentioning
confidence: 99%
“…In another recent twist, the crosslinking of alginate with glutaraldehyde has been also explored [11;12]. Nevertheless, the complete removal of toxic crosslinking chemicals is difficult and thus may be inappropriate for its application in food processing industries [13].…”
Section: Introductionmentioning
confidence: 99%